142 Update on familial thoracic aortic aneurysm disease in the 100, 000 genomes project: space for discovery. (May 2019) - Francis, Catherine; Jamshidi, Yalda; Gkoutos, George; Keavney, Bernard; Clift, Paul; Fowler, Tom
Abstract : Background: The 100, 000 Genomes Project offers an unprecedented opportunity to leverage whole genome sequencing data to characterise the hereditary basis of Familial Thoracic Aortic Aneurysm Disease (FTAAD). FTAAD is a heterogeneous group of syndromic and isolated aortopathies. The genetic basis of this presentation often remains undiscovered. Purpose: To define the FTAAD cohorts available in the 100, 000 Genomes Project and assess the current diagnostic yield and space for future discovery. Materials and methods: As of February 2019, 536 probands with FTAAD and HPO terms for thoracic aortic disease have been recruited to the 100, 000 Genomes Project. Inclusion criteria included: Thoracic aortopathy <50 years with no additional risk factors or Marfan syndrome with no identified FBN1 mutation or Loeys-Dietz syndrome or related condition, and Negative initial genetic screening to include FBN1, TGFBR1&2, ACTA2 where appropriate. Whole genome sequencing, quality control and filtering was carried out by Genomics England as previously described. Aortopathy genes are defined in PanelApp, an expert-curated gene list with validated associations with FTAAD. Genes curated for only skeletal phenotypes (eg FBN2, FLCN) with no evidence for aortic involvement were excluded. Tier 1 variants are rare and protein-truncating; tier 2 variants are rare and protein-altering. Tiered variants were excluded if Clinvar status was benign, or if they were not fully penetrant. Results: The cohort has a mean age of 44 years (range 0–79). 110 probands were <30 years old at disease onset. 113 probands had a history of aortic dissection. 96 had additional aortic valve abnormalities, with 36 reported as bicuspid. Only 22 were reported to have significant AR or AS. Skeletal abnormalities were prevalent, with 66 having sternal abnormalities. Only 8 Tier 1 variants in validated aortopathy genes were reported in this cohort. These were in BGN, FBN1, LOX, MYH11, MYLK, TGFB2 and TGFBR1 (see table1). This defines a diagnostic yield of just 8/536 (6%) in this patient group, using known aortopathy gene panels. Surprisingly, none of these variants were found in probands under 30 at disease onset. There were 68 classic trios in this cohort (proband + mother and father). However, just one of these has a clearly pathogenic de novo variant identified (in MYH11). There were just 2 Tier 2 variants of uncertain significance (VUS) in aortopathy genes in other trios. 10 larger family structures have yielded no clear pathogenic candidates to date. The majority of the cohort are recruited as singletons. 75 Tier 2 variants have been identified to date in 19 aortopathy genes (see figure 1). Just 1 of these (in LOX) can be classified as likely pathogenic. The remainder are VUSs. Conclusion: In this genetically pre-screened cohort with FTAAD, genetic diagnosis remains elusive. The variety of genes in which protein-altering variants are found highlights the genetic heterogeneity of this condition. We plan further systematic studies of the family structures available in the 100, 000 Genomes Project and case:control studies to further elucidate the genetic architecture of FTAAD. The negative findings to date, particularly in probands with young-onset aortopathy, make it likely that responsible genes are yet to be discovered in many cases. This research was made possible through access to the data and findings generated by the 100, 000 Genomes Project. Conflict of Interest: None